Optimum scheduling of non-utility facility with battery storage under a price-taking scheme - Somboon Nuchprayoon (2018)
© 2015 IEEE. Modeling of non-utility facility with generation and battery storage is presented. The operation strategy for non-utility facility is determined by solving a daily generation scheduling problem under a price-taking scheme. Numerical simulations are performed under various scenarios. It is shown that the optimal strategy is complex when either fuel supply is limited or electric utility allows buy-back option for non-utility facility. The impacts of price and load variations on the complexity of solutions are investigated. The sizing of battery storage device is also examined.